Old-Age Pension and Intergenerational Living Arrangements - Xi Chen (Institute for the Study of Labor (IZA), 2015)
China launched a pension program for rural residents in 2009, now covering more than 300 million Chinese. This program offers a unique setting for studying the ageing population, given the rapidity of China's population ageing, traditions of filial piety and co-residence, decreasing number of children, and dearth of formal social security, at a relatively low income level. This paper examines whether receipt of the old-age pension payment equips elderly parents and their adult children to live apart and whether parents substitute children's time involved in instrumental support to them with service consumption. Employing a regression discontinuity (hereafter RD) design to a primary longitudinal survey conducted in Guizhou province of China, this paper overcomes challenges in the literature that households eligible for pension payment might be systematically different from ineligible households and that it is difficult to separate the effect of pension from that of age or cohort heterogeneity. Around the pension eligibility age cut-off, results reveal large and significant reduction in intergenerational co-residence of the extended family and increase in service consumption among elderly parents.
Keywords: H55; I38; J14; J22; 330; rural pension; RD Design; living arrangement; service consumption